The Effect of Polyunsaturated Fatty Acids Omega-3 Supplementation on theComponents of Rheumatoid Arthritis Disease Activity: A Systematic LiteratureReview - Awalia (Indonesian Rheumatology Associantion, 2022)
Background: Rheumatoid arthritis (AR) is a chronic disease that causesdeformity in most productive age and can lead to death as disease activityincreases. Omega-3 polyunsaturated fatty acids (PUFAs) have the potentialto complement available therapies in reducing disease activity. Currently,the effect of omega-3 PUFAs on disease activity components is still unclear.This study aimed to determine the effect of omega-3 PUFAs’ supplementationon the components of RA disease activity. Methods: This research is asystematic study with PRISMA guidelines. Literature identification usingPubmed, MDPI, and clinicaltrials.gov. The inclusion criteria used were:giving omega-3 PUFAs, free full-text, RCT, in English or Indonesian, andassessing disease activity and its components; while the exclusion criteriawere: unpublished, comparisons were inappropriate. Assessment ofliterature quality with the Cochrane Collaboration tool. Results: The studyincluded six studies from 1994 to 2017. The effect of omega-3 PUFAs isdiversity in changes of disease activity in 4 of 5 studies. Another effect is asignificant reduction in the number of joint pains in the literature by dailydoses above 2.9 grams or at lower doses taking longer, and swollen joints in2 studies that were only affected in doses above 2.9 grams. Another changeis a significant reduction in pain severity in the studies. Change increaseswith higher doses. There are variable LED and CRP changes with minimalstudy resources. Conclusion: Omega-3 PUFAs depend on their dose andadministration duration and can, directly and indirectly, affect diseaseactivity through the influence of most of its components, namely: the numberof joints affected, the degree of pain, but the results of the ESR and CRPexaminations are not sufficient.